Vestigis de la tradició litúrgica narbonesa i de debitoris jueus en uns formularis medievals - Rubió i Serrat, Abel (Miscel·lània litúrgica catalana, 2019)
This paper presents the study of a medieval parchment containing notarial forms used near Manresa. There is an image of the Crucifixion presiding the four beginnings of the Gospels, accounting annotations, Jewish debitoria, a sampling of medieval letters and an establishment form. Thebeginnings of the Gospels were used in the consecration of churches in Catalonia according to the Narbonese liturgy until the 13th century. It may also be seen that there was a Jewish presence in this period in which notarial documentation came to acquire considerably more importance in Manresa. This parchment has come down to us through the Fàbregas family, which has conserved it in their family archive.